Desenvolvimento de um sistema para aquisição e armazenamento de dados baseado na plataforma Arduino - MARTINS, Anastaciane Pinto (2018)
This study aimed to develop a tool for data acquisition and storage system for monitoring the displacement of the axis of the second HPP hydro power house - Tucuruí. At the plant in question there is a monitoring system, including VibroSystM, which has since the sensors that capture the physical parameters and transduce into an electrical signal, to the system that converts analog signals to digital and stores them in its own database however, there is a need for information relating to the axes of hydro have their easy access and are recorded with the greatest possible consistency. To achieve the objectives of this work was carried out a study of data acquisition systems and from this it was decided to use a microcontroller system based on the Arduino platform. The built prototype uses a mass storage device (SD memory card) to store important data for further analysis, communicating with the main board (Arduino Uno) through a plate that adds extra functionality to the main board (Shield). In addition, an RTC (real time clock) was necessary to indicate the instant of home purchase. This set of devices in the datalogger was called Arduino SD work. He was coupled to VibroSystM system. Developed both the software and the necessary hardware and set up the database with system information. Additionally, it was possible to apply a simple routine to analyze the data stored on the SD card, allowing the user to draw and visualize the behavior of your system.